Electrochemical organization of monolayer protected gold nanoclusters on single-walled carbon nanotubes: significantly enhanced double layer capacitance - Mahima, Subhramanyam; Chaki, N. K.; Sharma, J.; Kakade, Bhalchandra A.; Pasricha, R.; Rao, A. M.; Vijayamohanan, K. (Journal of Nanoscience and Nanotechnology, 2006)
This paper reports a novel electrochemical route for anchoring monolayer protected gold nanoclusters (size 8 +/- 0.2 nm) on single-walled carbon nanotube bundles, resulting in the formation of hybrid materials. Monolayer protected gold nanoclusters prepared by modified Brust synthesis route were organized on SWNT bundles by cycling-the potential in dichloromethane between -1 to +1 V at a scan rate of 50 mV/s. Monolayer protected nanoclusters in electrolyte solutions possess ionic space charge around them (double layer charging), making them suitable for organization on nanotube bundles, by tuning the electrostatic interactions. More significantly, analysis of the double layer capacitance of these hybrid materials shows almost ten times increase in capacitance compared to that of bare SWNT bundles. We believe that these hybrid materials are potentially useful in nanoelectronics.
Keywords: double layer capacitance; double layer charging; hybrid materials; monolayer protected gold nanoclusters; single-walled carbon nanotubes

High-purity synthesis of scrolled mats of multi-walled carbon nanotubes using temperature modulation - Kakade, Bhalchandra A.; Allouche, Hatem; Mahima, Subhramanyam; Sathe, Bhaskar R.; Pillai, Vijayamohanan K. (Carbon, 2008)
Felt-like mats (6-7 mu m thick) of multimalled carbon nanotubes wrapped into scrolls have been synthesized by chemical vapor deposition from a toluene-ferrocene mixture using a temperature ramp from 680 degrees C to 550 degrees C in hydrogen-argon atmosphere. Thermogravimetric analysis reveals a very low catalyst content of ca. 1.25 wt% in the as-synthesized sample while, X-ray photo electron and Raman spectroscopies suggest the results matching with that of multiwalled carbon nanotubes. Considering, different time scales of various reactions and the diffusion of different reactants and products a tentative base growth mechanism has been proposed as per the available characterization data in conjunction with possible scrolling effects. Thermal expansion effects could explain a tentative mechanism for rolling action of sheets. Interestingly, electrical conductivity measurements as a function of temperature suggest a semiconducting behavior, despite being governed by different electron transport mechanisms with activation energies of 0.33 and 1.03 meV corresponding to two temperature ranges respectively. Cyclic voltammetry and electrochemical impedance analysis show a reversible redox behavior due to very low catalyst content and an irreversible etching of the Fe catalyst after acid treatment. (C) 2007 Elsevier Ltd. All rights reserved.

Synthesis of platinum Y-junction nanostructures using hierarchically designed alumina templates and their enhanced electrocatalytic activity for fuel-cell applications - Mahima, Subhramanyam; Kannan, Ramaiyan; Komath, Indulekha; Aslam, Mohammed; Pillai, Vijayarnohanan K. (Chemistry of Materials, 2008)